(untitled) (Research, Society and Development, 2020)
Considering that scientific education is important for individual development and insertion in society, the present work seeks to conceptualize the expressions scientific literacy and scientific lettering. The reflections depart from the framework of language for later transposition to the area of science teaching. It is proposed that despite points of convergence and approximation, the terms scientific literacy and scientific lettering cannot be taken as synonyms and it is suggested that scientific literacy consists of levels of scientific lettering. To defend the proposition practical contributions are presented. Finally, we reaffirm that scientific literacy and scientific lettering are distinct aspects of and for science education.